'My President is a Pair of Buttocks': the limits of online freedom of expression in Uganda. (19th July 2018) - Rukundo, Solomon
Abstract: On the 27 of January 2017, human rights activist, Dr Stella Nyanzi, wrote a post on Facebook in which she dubbed the Ugandan president 'a pair of buttocks'. Since then she has been subjected to various forms of harassment by the state culminating in her arrest on 7 April 2017 when she was charged with cyber harassment and offensive communication contrary to sections 24 and 25 of the Computer Misuse Act (CMA), respectively. Her case is emblematic of the shrinking space for free expression in the Ugandan cyberspace. While the Internet is frequently hailed as a tool for individual free expression, this is not the case in Uganda where the state is using the Computer Misuse Act, specifically sections 24 and 25, to limit online freedom. This article analyses the case of Dr Nyanzi arguing that sections 24 and 25 of the CMA are unconstitutional as they limit online freedom.